Green IT attitude and behaviour in higher education institution: a gender perspective - Kartiwi, Mira; Gunawan, Teddy Surya; Hasan, Helen (Asian Network for Scientific Information, 2014)
As a response to the growing concerns of the global warming and climate change, more and more organizations adopted environmental initiatives as part of their organizational ethos. Many higher education institutions (HEIs), particularly, have implemented various on campus environmental initiatives through policy as well as teaching and learning activities. Despite the growing awareness of global environmental issues in education sector, little is known on how effective such initiatives in shaping the perception and behaviour of the students. Previous research also highlighted the differences on technology use and perspective between genders. Given the limited study in this domain, therefore, it is the aim of this paper to evaluate the influence of gender on students’ green attitudes and behaviour. The result of this study shows the needs to inculcate basic computer technical knowledge and skills so as to minimize the ‘technical knowledge gap’. This is an imperative step to close, or at least to narrow, the gender discrepancy in regards to attitude and behaviour towards green IT initiatives.